Networks of pre-diagnostic circulating RNA in testicular germ cell tumour - Joshua Burton; Trine B. Rounge; Trine B. Haugen; Marcin W. Wojewodzic (Scientific Reports, 2025)
Abstract Testicular germ cell tumour (TGCT) is a malignancy with known inherited risk factors, affecting young men. We have previously identified several hundred differentially abundant circulating RNAs in pre-diagnostic serum from TGCT cases compared to healthy controls. In this study, we performed Weighted Gene Co-expression Network Analysis (WGCNA) on mRNA and miRNA data from these samples. Central genes (hub genes) enriched functional pathways, and regulatory feature prediction were identified for all TGCT subtypes together and according to histology. The TGCT susceptibility genes TEX14, NARS2, and G3BP2, were identified as hub genes in both seminoma and non-seminoma networks. We also identified UBCA1, RCC1, FMR1, OAS3, and UBE2W as hub genes associated with TGCT. The genes OAS3 and UBE2W have previously been associated with testicular dysgenesis. Furthermore, network module analysis indicated transcription factors for oestrogen-related receptors to have a potential role during development of TGCT. The overlap between mRNA network hub genes and TGCT susceptibility genes indicates a common role in TGCT development.